KEMAMPUAN MANAJERIAL KEPALA SEKOLAH DALAM MANAJEMEN SEKOLAH DI SMP NEGERI KECAMATAN ARUNGKEKE KABUPATEN JENEPONTO - Maliling, Maliling (Eklektika: Jurnal Pemikiran dan Penelitian Administrasi Pendidikan, 2016)
The objective was to determine the ability of planning, organizing, directing, This type of research is descriptive qualitative research. Source is the principal, vice principal and junior high school teachers in the District Arungkeke Jeneponto. Data collection techniques used were interviews, observation and documentation. The collected data was then analyzed with qualitative methods with the following steps, namely: data collection, data reduction, the present data, verification data and concludes the research.The results showed that the managerial ability of the head of the Junior High School School District Arungkeke Jeneponto can be seen from the ability penrencanaan principals in developing strategic, operational planning, annual planning, demand planning and school budgets are based on knowledge management and intelligent leadership.